2003
DOI: 10.1111/j.1475-5890.2003.tb00091.x
|View full text |Cite
|
Sign up to set email alerts
|

Ownership and Production Costs: Choosing between Public Production and Contracting‐Out in the Case of Swedish Refuse Collection

Abstract: Many comparisons of public and private firms use a public/private ownership dummy variable to capture cost differences. If, however, public and private firms use different production technologies, the dummy‐variable approach is misspecified. Data from public and private firms should not be pooled. Secondly, selectivity bias may arise, making it more difficult to identify cost differentials that actually exist. Thirdly, if data should be pooled, the resulting empirical model may be logically inconsistent. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(72 citation statements)
references
References 38 publications
2
69
0
1
Order By: Relevance
“…Additionally, such an approach can provide results which while more general, are more robust, and capture the decision to privatise more appropriately. The first 2 They include Ferris (1986); Morgan, Hirlinger and England (1988); Benton and Menzel (1992); Miranda (1994); Greene (1996); Nelson (1997) (McGuire, Ohsfeldt and van Cott, 1987;Dijkgraaf, Gradus and Melenberg, 2003;Walls, Macauley and Anderson, 2005), while others are unable to make this confirmation (Ferris and Graddy, 1988;Ohlsson, 2003). However, when scale economies are combined with the transaction costs deemed likely as a result of privatisation, there is evidence that privatisation is more probable in services with lower transaction costs (Ménard and Saussier, 2000;Walls, Macauley and Anderson, 2005;Bel and Fageda, 2008).…”
Section: Intermunicipal Cooperation and Privatisation: Empirical Backmentioning
confidence: 99%
“…Additionally, such an approach can provide results which while more general, are more robust, and capture the decision to privatise more appropriately. The first 2 They include Ferris (1986); Morgan, Hirlinger and England (1988); Benton and Menzel (1992); Miranda (1994); Greene (1996); Nelson (1997) (McGuire, Ohsfeldt and van Cott, 1987;Dijkgraaf, Gradus and Melenberg, 2003;Walls, Macauley and Anderson, 2005), while others are unable to make this confirmation (Ferris and Graddy, 1988;Ohlsson, 2003). However, when scale economies are combined with the transaction costs deemed likely as a result of privatisation, there is evidence that privatisation is more probable in services with lower transaction costs (Ménard and Saussier, 2000;Walls, Macauley and Anderson, 2005;Bel and Fageda, 2008).…”
Section: Intermunicipal Cooperation and Privatisation: Empirical Backmentioning
confidence: 99%
“…For instance, Domberger and Jensen's (1997) overview of contracting out shows cost savings of up to 20 percent without sacrificing the quality of service provided. In contrast, Ohlsson (2003) found that contracted out refuse collection service in Sweden cost significantly more than those provided by local government. Clearly, assumptions about automatic efficiency through contracting out need to be tempered.…”
Section: Resultsmentioning
confidence: 48%
“…Nevertheless, a surprising result has been achieved by the variable called distance to landfi ll / incinerator. Despite the fact that a positive dependency was expected in compliance, for instance, with Callan and Th omas (2001), Ohlsson (2003), Bel and Costas (2006) or Dijkgraaf and Gradus (2006), the results have confi rmed rather a negative de-pendency. Th is result may indicate a more signifi cant role of a fee for use of a landfi ll / incinerator than the distance.…”
Section: Resultsmentioning
confidence: 82%
“…Callan and Th omas 2001;Dijkgraaf and Gradus 2003;Ohlsson 2003;Bel and Costas 2006;Sø-rensen 2007;Bel and Mur 2009;Dijkgraaf and Gradus 2013;Zafra-Gómez et al 2013;Gradus et al 2014;Soukopová et al 2014;Bel and Warner 2008;Soukopová et al 2016). Regardless of this broad discussion, there is no general agreement whether the local governments should prefer to deliver their services as producers or providers.…”
Section: Introductionmentioning
confidence: 99%